2001
DOI: 10.1007/s002680020107
|View full text |Cite
|
Sign up to set email alerts
|

Systolic and Diastolic Properties and Myocardial Blood Flow in the Heterotopically Transplanted Rat Heart during Acute Cardiac Rejection

Abstract: The aim of the study was to characterize the course of systolic and diastolic function, myocardial blood flow, and histologic changes during acute rejection in a model of heterotopic transplantation in rats. For this purpose isogenic Lewis-to-Lewis and allogenic DA (Dark Agouti)-to-Lewis rat cardiac transplants were studied 1 hour and 1, 3, and 5 days, respectively, after heterotopic intraabdominal transplantation. Myocardial tissue blood flow (MBF) was assessed by the hydrogen-clearance method. An implanted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…In agreement with our previous studies 2, 9 we observed a typical sequence of cardiac dysfunction during the development of acute cardiac rejection: preserved baseline systolic and diastolic function with reduced contractile reserve at the stages of mild to moderate rejection, followed by progressive systolic and diastolic dysfunction during severe rejection. Reduced responsiveness to ␤-adrenergic stimulation at preserved baseline contractility has been also described at early stages of cardiac rejection in ventricular myocytes, 14 isolated papillary muscles, 15 ex vivo Langendorff preparation 16 and rejecting canine orthografts.…”
Section: Discussion Graft Function and Survivalsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our previous studies 2, 9 we observed a typical sequence of cardiac dysfunction during the development of acute cardiac rejection: preserved baseline systolic and diastolic function with reduced contractile reserve at the stages of mild to moderate rejection, followed by progressive systolic and diastolic dysfunction during severe rejection. Reduced responsiveness to ␤-adrenergic stimulation at preserved baseline contractility has been also described at early stages of cardiac rejection in ventricular myocytes, 14 isolated papillary muscles, 15 ex vivo Langendorff preparation 16 and rejecting canine orthografts.…”
Section: Discussion Graft Function and Survivalsupporting
confidence: 92%
“…Isogeneic and allogeneic (Lewis to Lewis and DA to Lewis, respectively) heterotopic abdominal cardiac transplantations were performed by one surgeon using the technique of Ono and Lindsay, as previously described. 9,10 In the first series of experiments, animals with allogeneic grafts were treated with either: vehicle; water-soluble PARP inhibitor INO-1001 1 mg/kg/day intraperitoneally (Inotek Pharmaceuticals, Beverly, MA); cyclosporine 2.5 mg/kg/day orally; cyclosporine 5 mg/ kg/day orally; or the combination of INO-1001 and low-dose cyclosporine (n ϭ 6 transplanted animals/ group). This cohort of animals was used to determine the duration of allograft survival by evaluating the heart beat daily by palpation.…”
Section: Materials and Methods In Vivo Experimentsmentioning
confidence: 99%
“…8 A study in rats demonstrated that myocardial blood flow assessed by the hydrogen-clearance method recovered during the first day after transplantation in both allografts and isografts but decreased again in allografts 3 days after transplantation, which was followed by systolic dysfunction at day 5. 27 In the present study, MCE based on destructionreplenishment dynamics 25 revealed a significant reduction of myocardial perfusion in the untreated allografts but not in the allografts treated with high-or low-dose CsA. Thus, perfusion imaging was insensitive to any abnormalities in allografts treated with CsA at posttransplantation day 3.…”
Section: Kondo Et Al Allograft Rejection With Contrast Echomentioning
confidence: 71%
“…Thus, the left uterine horn was removed after placements of two titanium clips; one just caudal to the Fallopian tube and the second one just cranial to the uterine bifurcation from the common uterine cavity. The median and range of the total surgery time for the Sham-operated animals were 21 minutes [17][18][19][20][21][22][23][24][25].…”
Section: Methodsmentioning
confidence: 99%
“…Although this Dark Agouti-to-Lewis allogeneic rat model has been used in research on other types of organ transplantations, with proven prominent rejection under non-immunosuppressed conditions (18,19), we tested three animals with uterine grafts and no immunosuppression. After 10 days all showed rejected graft with massive necrosis.…”
Section: Bmentioning
confidence: 99%